Simplification
- 50 / ? = ? / 121/2
-
View Hint View Answer Discuss in Forum
Let 50 / N = N / (25/2)
⇒ N2 = 50 x 25/2 = 625Correct Option: D
Let 50 / N = N / (25/2)
⇒ N2 = 50 x 25/2 = 625
∴ N = √625 = 25
- If x/y = 4/5, then the value of 4/7 + (2y - x)/(2y + x) is ?
-
View Hint View Answer Discuss in Forum
Given Exp. = 4/7 + (2y - x)/(2y + x)
= 4/7 + [(2 - (x/y)] / [2 + (x/y)]
= 4/7 + [2 - 4/5] / [2 + 4/5]
= 4/7 + ( 6/5 x 5/14 )Correct Option: B
Given Exp. = 4/7 + (2y - x)/(2y + x)
= 4/7 + [(2 - (x/y)] / [2 + (x/y)]
= 4/7 + [2 - 4/5] / [2 + 4/5]
= 4/7 + ( 6/5 x 5/14 )
= 4/7 + 3/7
= 1
- If x/2y = 3/2, the value of (2x + y) / (x - 2y) equals ?
-
View Hint View Answer Discuss in Forum
Given expression = 2x + y / x - 2y
Dividing Num and Denom by y we get.
= [2(x/y) + 1] / [(x/y) - 2] = (2 x 3 + 1) / (3 - 2) = 7/1 = 7
[ ∵ x/2y = 3 / 2 ⇒x/y = (3 / 2 x 2) = 3 ]Correct Option: B
Given expression = 2x + y / x - 2y
Dividing Num and Denom by y we get.
= [2(x/y) + 1] / [(x/y) - 2] = (2 x 3 + 1) / (3 - 2) = 7/1 = 7
[ ∵ x/2y = 3 / 2 ⇒x/y = (3 / 2 x 2) = 3 ]
- (885 x 885 x 885 + 115 x 115 x 115) / (885 x 885 + 115 x 115 - 885 x 115) is equal to ?
-
View Hint View Answer Discuss in Forum
Given expression = (a3 + b3) / (a2 + b2 - ab)
= (a + b)(a2 + b2 - ab) / (a2 + b2 - ab)Correct Option: D
Given expression = (a3 + b3) / (a2 + b2 - ab)
= (a + b)(a2 + b2 - ab) / (a2 + b2 - ab)
= (a + b) = (885 + 115)
= 1000
- 42/17 ÷ 12/5 x 22/33 = ?
-
View Hint View Answer Discuss in Forum
Give expression
= 70/17 ÷ 7/5 x 68/33
= 70/17 x 5/7 x 68/33
= 200/33Correct Option: B
Give expression
= 70/17 ÷ 7/5 x 68/33
= 70/17 x 5/7 x 68/33
= 200/33
= 62/33